2017
DOI: 10.1016/j.diabres.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

General and diabetes-specific stress in adolescents with type 1 diabetes

Abstract: Background Type 1 diabetes (T1D) is one of the most common chronic health conditions in adolescents in the United States. Adherence to the recommended treatment regimen has been reported as a source of stress for adolescents. Aim The purpose of this study was to examine the associations among general and diabetes-specific stress and glycemic control (HbA1c), self-management, and diabetes-specific quality of life (QOL) in adolescents with T1D. Methods A secondary analysis of baseline data (N = 320) from a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 33 publications
5
51
1
8
Order By: Relevance
“…Another study by Thomas et al, who surveyed 9310 45-year-old participants from the 1958 British birth cohort, also showed that household dysfunction and lack of paternal care during childhood was associated with HbA1c ≥6% [19]. Rechenberg et al conducted a questionnaire based study involving 320 children with T1DM of ages 11-14 years, which showed those participants who underwent general stress and diabetes specific stress had significantly elevated HbA1c [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Thomas et al, who surveyed 9310 45-year-old participants from the 1958 British birth cohort, also showed that household dysfunction and lack of paternal care during childhood was associated with HbA1c ≥6% [19]. Rechenberg et al conducted a questionnaire based study involving 320 children with T1DM of ages 11-14 years, which showed those participants who underwent general stress and diabetes specific stress had significantly elevated HbA1c [20].…”
Section: Discussionmentioning
confidence: 99%
“…For persons with T1D, stress has the potential to affect metabolic control directly through its impact on cortisol and other catecholamine hormones that affect insulin metabolism . However, stress has also been shown to affect metabolic control indirectly by interfering with the completion of daily diabetes management tasks or increasing psychological symptoms (ie, depression) that negatively affect diabetes management . Decreased family support for illness management tasks among emerging adults with T1D may make the transition to adulthood particularly stressful .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a stressful and demanding developmental period, both biologically and psychosocially (Jaser & White, ; Seiffge‐Krenke, Aunola, & Nurmi, ). Adolescents with T1D have high levels of perceived stress, both general and diabetes‐specific (Chao et al, ; Grant et al, ; Rechenberg, Whittemore, Holland, & Grey, ). It is known that managing diabetes is a stressful and time‐consuming endeavor (Chao et al, ; Delamater, de Wit, McDarby, Malik, & Acerini, ; Rechenberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with T1D have high levels of perceived stress, both general and diabetes‐specific (Chao et al, ; Grant et al, ; Rechenberg, Whittemore, Holland, & Grey, ). It is known that managing diabetes is a stressful and time‐consuming endeavor (Chao et al, ; Delamater, de Wit, McDarby, Malik, & Acerini, ; Rechenberg et al, ). Our results support the extant literature that youth with T1D experience heightened general and diabetes‐specific stress, and that both are important, but are experienced differently (Chao et al, ; Rechenberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation